Controlling the Antioxidant Activity of Green Tea Extract through Encapsulation in Chitosan-Citrate Nanogel. (3rd July 2020) - Piran, F.; Khoshkhoo, Z.; Hosseini, S. E.; Azizi, M. H.
Abstract : Applying bioactive ingredients in the formulation of foods instead of artificial preservatives is problematic because bioactive ingredients are unstable and sensitive to environmental conditions. The present study aimed to control the antioxidant activity of green tea extract (GT) through encapsulating in chitosan nanoparticles (CS-NP). The synthesized nanoparticles were analyzed by using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). The encapsulation efficiency (EE), particle size, zeta potential, and polydispersity index (PDI) of GT-loaded CS-nanoparticles (CS-NP-GT) were assessed. Based on the results, the particle size and zeta potential related to the ratio of CS to GT of 1 : 0.5 were obtained as 135.43 ± 2.52 nm and 40.40 ± 0.2 mV, respectively. Furthermore, the results of FT-IR and XRD confirmed the validity of encapsulating GT in CS-NP. In addition, the antioxidant activity of GT increased after nanoencapsulation since the IC50 value of CS-NP-GT decreased to 6.13 ± 0.12 μ g/ml. Finally, applying these particles for delivering GT polyphenols in foods is regarded as promising.